Study of uniformly doped nano scale single-walled CNTFET under dark and illuminated conditions. (October 2020) - Arulmary, A.; Rajamani, V.; Kavitha, T.
Abstract: Advancement in technology has resulted in transistors scaling down to nanometers. The evolution has resulted in investigations which extend to the structure of nanometer devices and the theories related to them. The extent of the investigation has stepped into Single-walled carbon nanotube field effect transistor (SW-CNTFET). The numerical method of self-consistent 3D Poisson and Schrödinger equations is solved by the Leibmann's iteration method. Further, study the effect of illumination on different parameters including the surface potential, drain current, mobility, transconductance and sub-threshold of n-type SW- CNTFET with high-k gate dielectric constant. Finding is that the use of Hfo2 high-k dielectric enhances the device characteristics. Comparing the drain current in illumination and dark condition, there is a notable increase when illuminated. The simulated results of proposed CNTFET photo detector were compared with existing MOSFET photo detector. Better drain current, transconductance and cut off frequency were obtained for the CNTFET. This result is in very much agreement with results obtained from numerical simulations. These findings on optical properties of carbon nanotubes (CNTFET) are sure to advance the fields of photo detectors, OEIC, solar cells and IC fabrications.